2021
DOI: 10.1186/s13287-021-02615-z
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cells can improve thrombolytic effect of low-dose rt-PA after acute carotid thrombosis in rat

Abstract: Background Intravenous thrombolysis using recombinant tissue plasminogen activator (rt-PA) is the standard treatment for acute ischemic stroke. Standard-dose rt-PA (0.9 mg/kg) is known to achieve good recanalization but carries a high bleeding risk. Lower dose of rt-PA has less bleeding risk but carries a high re-occlusion rate. We investigate if induced pluripotent stem cells (iPSCs) can improve the thrombolytic effect of low-dose rt-PA (0.45 mg/kg). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…iPSCs exhibit multiple effects in treating IS, including migration to ischemic brain tissue, differentiation into neurons, pro-inflammatory factor down-regulation, and anti-inflammatory factor up-regulation, eventually improving motor function [86] . Meanwhile, iPSCs enhance the thrombolytic effect of low-dose tissue plasminogen activators [87] . A recent study found that small EVs derived from iPSCs can rejuvenate the blood-brain barrier of aged mice, preventing IS occurrence [88] .…”
Section: Current Status Of Sc Therapy On Ismentioning
confidence: 99%
“…iPSCs exhibit multiple effects in treating IS, including migration to ischemic brain tissue, differentiation into neurons, pro-inflammatory factor down-regulation, and anti-inflammatory factor up-regulation, eventually improving motor function [86] . Meanwhile, iPSCs enhance the thrombolytic effect of low-dose tissue plasminogen activators [87] . A recent study found that small EVs derived from iPSCs can rejuvenate the blood-brain barrier of aged mice, preventing IS occurrence [88] .…”
Section: Current Status Of Sc Therapy On Ismentioning
confidence: 99%
“…Several studies have verified the protective effects of MSCs on the nervous system 31,32 . In particular, WJMSCs can attenuate neurodegeneration, and they are widely used as a therapeutic treatment for neurological diseases such as ischemic stroke, traumatic brain injury, neonatal hypoxia‐ischemia, and Alzheimer's disease because of their stimulatory effect on trophic and immunoregulatory factors 25,33–3536 …”
Section: Introductionmentioning
confidence: 99%